The Mapparola Tradition in Marriage Practices of the Belawa District Community, Wajo Regency - Rudin, Syafaat; Ashar, Ashar (Universitas Ibn Khaldun Bogor, 2025)
This thesis discusses Mapparola in the marriage customs of the Bugis Wajo community. The main issue is the implementation of the Mapparola tradition in marriages for the community in Belawa Siattinge District, Wajo Regency, and its perspective according to Islamic law. This research is a field study using qualitative methods and employs two approaches: sociological and empirical. The data in this study were obtained from interviews with cultural leaders, religious leaders, and individuals considered knowledgeable in Islamic law, including the Head of the Religious Affairs Office (KUA) of Belawa District, Islamic Religious Counselors, and cultural leaders who understand the culture in Wajo Regency. The aim of this research is to understand the process of implementing the Mapparola tradition in marriage and to comprehend the views of the Belawa community, Wajo Regency, regarding this tradition in the context of marriage. The Mapparola tradition is one of the local cultural heritages that is still preserved by the community as part of the marriage customs. The method used in this research is qualitative with a descriptive approach. Data were collected through observation, in-depth interviews, and documentation involving cultural leaders, newlywed couples, and local communities. The results of the study indicate that the Mapparola tradition has specific stages that are rich in symbolic and cultural values, such as respect for the families of the bride and groom, mutual cooperation, and values of politeness. The Belawa community views this tradition as an important part of maintaining cultural identity and strengthening social ties between families. Although it has undergone some adjustments in its implementation, the Mapparola tradition remains a respected element in the traditional marriage process in the region.